Pregnant Employee Protection Program in a Large Chemical Company. Issue 9 (September 2015) - Frey, Gunild; Schuster, Michael; Oberlinner, Christoph; Queißer-Wahrendorf, Annette; Lang, Stefan; Yong, Mei
<x xml:space="preserve">Abstract</x> Objectives: To assess whether a structured employee protection program for pregnant workers at a chemical company has an impact on pregnancy outcomes. Methods: Reported pregnancies (n = 1402) between 2003 and 2010 and their outcomes were documented using questionnaires at the time of pregnancy report, end of pregnancy, and 1 year later. Potential maternal exposures were assessed using job histories, workplace inspections, and questionnaires. Results: Participation was 86% overall and was consistently high across subgroups. Pregnancy losses (10.9%), pregnancy complications, and preterm births (8.1%) were in agreement with rates in the general population and were independent of type of work and maternal exposure category. Conclusions: Pregnancy complication rates in this chemical company are not statistically elevated than that in the general population, as suggested in a previous study. The protection program may play a role in preventing complications that may have occurred.